Os desafios enfrentados pelos alunos do curso de pedagogia para inserção no ensino superior - Bassotto, Simone Aparecida Silva Angelo (2012)
This study aimed to investigate the challenges faced by students of the Pedagogy course at two Universities in São Paulo when joining College. Dialogues were established with authors who disclosed the complexities of higher education processes. . Bauman (2007) deals with matters relating to the speed of events that drive adults to seek training; Boutinet (1999) investigates the challenges of adulthood and its confrontations and Silva (2011) writes about the new social strata that are entering this level of education in Brazil. Authors like Libâneo (2004), Freire (1996) and Pimenta (2005), contribute to broaden understanding about the formation of the pedagogue. The methodology was based on a qualitative approach (BOGDAN E BIKLEM, 1999). The research subjects were students in their last semester of Pedagogy course of the two Universities. Data collection was based on focus group technique (GATTI, 2005). Data analysis was performed based on content analysis (FRANCO, 2003). Results showed that students had difficulties in several dimensions, when entering higher education: the ongoing external difficulties; family and emotional; difficulties related to the physical structure of the university; difficulties with the course and the relationship with teachers; difficulties with the acquisition of theoretical knowledge and difficulties with interpersonal relationships. The research findings point to the need of Pedagogy courses invest in order to understand and accept their students so they can really be placed on their activities